Cytochrome P450s CYP380C6 and CYP380C9 in green peach aphid facilitate its adaptation to indole glucosinolate‐mediated plant defense. Issue 1 (20th August 2020) - Ji, Rui; Lei, Jiaxin; Chen, Ivy W; Sang, Wen; Yang, Shiying; Fang, Jichao; Zhu‐Salzman, Keyan
Abstract: BACKGROUND: Overexpressing CIRCADIAN CLOCK ASSOCIATED1 in Arabidopsis thaliana ( CCA1‐ox ) increases indole glucosinolate production and resistance to green peach aphid ( Myzus persicae ). Little is known of how aphids respond to this group of plant defense compounds or of the underlying molecular mechanism. Results: Aphids reared on CCA1‐ox for over 40 generations (namely the CCA population) became less susceptible to CCA1‐ox than aphids maintained on the wild‐type Col‐0 (namely the COL population). This elevated tolerance was transgenerational as it remained for at least eight generations after the CCA population was transferred to Col‐0. Intriguingly, transcriptome analysis indicated that all differential cytochrome P450 monooxygenase genes ( MpCYPs ), primarily MpCYP4 s, MpCYP380s and MpCYP6 s, were more highly expressed in the CCA population. Application of a P450 inhibitor to the CCA population resulted in decreased aphid reproduction on CCA1‐ox, which was not observed if aphids were reared on Col‐0. When indole glucosinolate biosynthesis in CCA1‐ox was blocked using virus‐induced gene silencing, the effect of the P450 inhibitor on the CCA population was attenuated, affirming the essential role played by MpCYPs in counteracting the defense mechanism in CCA1‐ox that is low or absent in Col‐0. Furthermore, we used host‐induced gene silencing to identify MpCYP380C6 and MpCYP380C9 that specifically facilitated the CCA population to cope with CCA1 ‐mediated plant defense. Expression profiles revealed their possible contribution to the transgenerational tolerance observed in aphids. Conclusion: MpCYP380C6 and MpCYP380C9 in aphids play a crucial role in mitigating indole glucosinolate‐mediated plant defense, and this effect is transgenerational. Abstract : Overexpression of CCA1 enhances plant resistance to aphids. CCA aphids can partly adapt to the resistant CCA1‐ox plants. Higher expression of MpCYPs in the CCA population is associated with its adaptation to elevated indole glucosinolates in CCA1‐ox. Two MpCYP380s have a significant contribution to aphid adaptation to indole glucosinolates. © 2020 Society of Chemical Industry